The Effect of Earnings Volatility on Stock Price Delay - Joong-Seok Cho (Scientific Annals of Economics and Business)
In this study, I examine the relation between earnings volatility and stock price response delay. I study the effect of the uncertainty of earnings and their components on the stock price response to value-relevant information. For more volatile earnings and earnings components, it is more complex for investors to reliably understand and impound information into stock prices. When earnings and components provide opaque and uncertain information about the future cash flows, I expect that investors are more divergent in their interpretations and delayed in arriving at their future cash flow estimates. To measure firms’ response to value-relevant information, I adopt a parsimonious measure of stock price response to information developed by Hou and Moskowitz (2005). I use five-year rolling standard deviations of earnings and components for earnings and components volatility measures. As an additional earnings volatility measure, I adopt the degree to which earnings volatility deviates from cash flow volatility. My study demonstrates that earnings volatility negatively affects stock price response to information. As I hypothesize, the more volatile earnings and components are, the more delayed the market reacts to value-relevant information. Among earnings and their components, the effect of cash flow volatility is the most influential.